Hard labor - Diamond, Susan L. (Forge, 1996)
In Hard Labor, Susan L. Diamond, B.S.N., R.N., shares a unique, insider's view of childbirth. Diamond's lifetime of experience - as a prepared-childbirth instructor, as an obstetrical nurse who spent nearly a decade working on labor and delivery wards, and as a mother of two - has given her an unmatched perspective on giving birth and on the impact of modern medicine on this most special time for mother and child. Too often in American hospitals today, the process of labor and delivery is treated as an illness, not as a natural, if life-altering, event. Women are dehumanized by artificially established "labor curves" and confined by often-unnecessary machinery; their personal needs, even their privacy, subsumed under the rules of the system. Fear of malpractice has added to the rigidity of the system - but so has a lack of true caring and a fondness for expediency.